ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENCEGAHAN FRAUD DI DALAM PROSES PENGADAAN BARANG DAN JASA - Larasati, Yarry Septia; Sadeli, Dadang; Surtikanti, Surtikanti (Universitas Pakuan, 2017)
The aim of this study is to obtain empirical data about the influence of internal control role, whistleblowing system, and good governance both partially and simultaneously to the prevention of fraud. This research involving 53 respondents in the scope of Directorate General of Marine Spatial Management Ministry of Marine Affairs and Fisheries, Republic of Indonesia. This research apply a survey by questionnaire as research instrument while methods used to process and analyze data on research are descriptive analysis and analysis of multiple regression. The results show that internal control role, whistleblowing system, and good governance have significant effects against fraud prevention partially, with count t larger than t table and positive value of regression. Furthermore, internal control role, whistleblowing system and good governance effect simultaneously to the prevention of fraud with the count f larger than f table. From this study, it can be concluded that internal control role, whistleblowing system and good governance whether partially and simultaneously effect prevention of fraud. Â Keywords: Â Internal Control, Whistleblowing System, Good Governance, Prevention of Fraud